An investigation into English and Vietnamese idioms denoting business - Lê, Ý Nhi. (2014)
This thesis is to investigate syntactic and semantic features of English and Vietnamese idioms denoting business, the researcher has used the combination of descriptive, analytical and contrastive methods in this investigation. Moreover, both quantitative and qualitative approaches are made used of investigation 360 samples in English and Vietnamese idioms from various sources such as dictionaries, books, newspapers, magazines, websites… The findings show that idioms denoting business have remarkable syntactic and semantic features and that there are some similarities and differences between the two languages. The researcher also dealt with the recommendations for teaching, learning and translating idioms as well as for further study.